Hysterium madraspatanum (Hysteriaceae), a new species from Tropical Dry Evergreen Forest of Tamil Nadu, India - Manogaran, Nivetha; Kayalvizhi A, Agnes; Munuswamy, Kumar (Phytotaxa, 2024)
A new species of Hysterium, is described from tropical dry evergreen forest region of Chennai, Tamil Nadu, India, based on both morphological characteristics and molecular phylogenetic analysis using the Internal Transcribed Spacers (ITS) region of nuclear ribosomal DNA. The key morphological characters of the ascomata include the presence of a longitudinal slit remaining closed even at maturity. The ascospores biseriate having three septa with all the cells evenly pigmented including the terminal cells. The ascus measuring 115–122 × 20–22 μm. Ascospores initially two celled and finally become four celled, hyaline first, later changing to yellow and then dark brown, oblong to ellipsoid, 28–39 × 7–12 μm. The nrITS-based phylogenetic tree inferred from the Bayesian posterior probabilities indicate that H. madraspatanum is closely related to Hysterium pulicare, H. angustatum and H. rhizophorae. However, H. madraspatanum is morphologically distinct from them by having relatively larger spore size, shallow groove in the ascomata, spores with concolorous terminal cells. Therefore, is a novel species under the genus Hysterium. Azadirachta indica is reported in the study as a new host for the genus Hysterium.